Whose standard is it, anyway? How the tobacco industry determines the International Organization for Standardization (ISO) standards for tobacco and tobacco products. Issue 2 (1st June 2001) - Bialous, Stella A; Yach, Derek
Abstract : OBJECTIVE: To describe the extent of the tobacco industry involvement in establishing international standards for tobacco and tobacco products and the industry influence on the International Organization for Standardization (ISO). METHODS: Analysis of tobacco industry documents made public as part of the settlement of the Minnesota Tobacco Trial and the Master Settlement Agreement. Search words included "ISO", "CORESTA", "Barclay", "compensation and machine smoking", "tar and nicotine deliveries", and the name of key players, in different combinations. RESULTS: It is clear that the tobacco industry, through the Cooperation Centre for Scientific Research Relative to Tobacco (CORESTA), play a major role in determining the scientific evidence and suggesting the standards that are eventually adopted as international standards for tobacco and tobacco products in several areas, including the measurement of cigarette tar and nicotine yield. CONCLUSIONS: ISO's tobacco and tobacco products standards are not adequate to guide tobacco products regulatory policies, and no health claims can be made based on ISO's tobacco products standards. There is an urgent need for tobacco control advocates and groups worldwide to be more involved with the work of the ISO, both directly and through their national standardisation organisations.